2014
DOI: 10.1111/1748-8583.12033
|View full text |Cite
|
Sign up to set email alerts
|

College students and HR professionals: conflicting views on information available on Facebook

Abstract: Increasingly employers are using social media as a mechanism to screen potential job candidates. This study examined college students' perceptions of the amount and degree of information available to potential employers who use social media. The study employed a survey of college students to determine how much information they felt someone could learn about them through their Facebook page. Results indicated that participants did not perceive much information about key job categories could be derived from thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 27 publications
0
7
0
2
Order By: Relevance
“…The remainder who did not manage their SNSs may be more typical of Curran et al . 's () college students, who planned few changes to webpages, as they did not believe employers would find them useful. This latter group may also reflect VanMeter et al .…”
Section: Discussionmentioning
confidence: 99%
“…The remainder who did not manage their SNSs may be more typical of Curran et al . 's () college students, who planned few changes to webpages, as they did not believe employers would find them useful. This latter group may also reflect VanMeter et al .…”
Section: Discussionmentioning
confidence: 99%
“…Also, they asked for opportunities for correction. Curran et al (2014) asked 12 college students to describe what they used SNSs for and what types of information they thought were available to others who looked at their sites. They found that college students are aware that potential employers will use SNSs to gather information about them, but at the same time, they are not overly concern about it.…”
Section: Cybervetting In the Hrm Domainmentioning
confidence: 99%
“…Los MS pueden ser profesionales o no-profesionales (El Ouirdi, Pais, Segers, y El Ouirdi, 2016), por lo que no tienen por qué proporcionar información relacionada con el puesto; existiendo un desequilibrio entre los propósitos de algunos MS y el uso que la organización hace de los datos obtenidos de los MS (Roth, Bobko, Van Iddekinge, y Thatcher, 2016). El sistema legal ha mantenido el derecho de una organización de revisar los MS como un elemento de información pública y, por consiguiente, soluciona el problema de la privacidad (Curran, Draus, Schrager, y Zappala, 2014), aunque el alcance de protección varía por países y frecuentemente los solicitantes de trabajo no están cubiertos por las normas reguladoras porque la relación con los empleados ocurre antes de que los acuerdos formales hayan sido realizados (Mc Donald, Thompson y O´Connor, 2016), llegando a experimentarse un creciente número de disputas en el trabajo relacionadas con los MS que han resultado en litigio entre los usuarios y las organizaciones que los emplean (Drouin, O´Connor, Schmidt, y Miller, 2015). ¿Pero es realmente importante el método a utilizar en la fase de reclutamiento?…”
Section: Revisión Literariaunclassified